2022
DOI: 10.21203/rs.3.rs-1585613/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of Medicago sativa extract and light on skin hypopigmentation disorders in C57/BL6 mice

Abstract: Vitiligo is a common depigmentation skin disease that affects the quality of life in many patients. This study aims to investigate the effect of Medicago sativa methanol extract on the treatment of skin hypopigmentation disorders. Antioxidant activity and phytochemical constituents of the extract were determined using DDPH assay, Folin-Ciocalteu, AlCl3 and HPLC-MS/MS analysis. Oil in water (o/w) creams were prepared to contain the methanolic extract, and applied to hydroquinone-induced depigmentation in vivo m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Data show that 200 μL of Nymphaea nouchali extract, applied on UVB-irradiated HRM-2 hairless mice at a concentration 100 µg/mL to a 3 cm × 3 cm designated area on the dorsal skin for 4 weeks exhibit antimelanogenic effects [ 107 ]. Medicago sativa extract used at 10% or 20% concentrations and administered to dorsal region of C57/BL6 mice for 4 weeks exhibit a remarkable skin and hair pigmentation [ 108 ]. A study conducted by Choi et al on UVB-irradiated brown guinea pig skin models revealed that Cyrtomium fortunei used at 3% concentration on back area and administered for 6 weeks exhibited depigmenting properties [ 109 ].…”
Section: The Effect Of Plant Extracts and Pure Compounds On Melanin C...mentioning
confidence: 99%
“…Data show that 200 μL of Nymphaea nouchali extract, applied on UVB-irradiated HRM-2 hairless mice at a concentration 100 µg/mL to a 3 cm × 3 cm designated area on the dorsal skin for 4 weeks exhibit antimelanogenic effects [ 107 ]. Medicago sativa extract used at 10% or 20% concentrations and administered to dorsal region of C57/BL6 mice for 4 weeks exhibit a remarkable skin and hair pigmentation [ 108 ]. A study conducted by Choi et al on UVB-irradiated brown guinea pig skin models revealed that Cyrtomium fortunei used at 3% concentration on back area and administered for 6 weeks exhibited depigmenting properties [ 109 ].…”
Section: The Effect Of Plant Extracts and Pure Compounds On Melanin C...mentioning
confidence: 99%